The in vitro anticancer effects of himachalol from Cedrus Libani. (c2017) - Elias, Andree M. (2017)
Cedrus libani, a member of the genus Cedar and family Pinaceae, is frequently used in traditional Lebanese medicine to treat several ailments. Essential oils extracted from this plant were found to exhibit important biomedical properties, including anti-ulcerogenic, anti-viral, neuroprotective as well as anti-proliferative activity. The present study aims to isolate himachalol, a major compound in the wood oil extract, and assess its anticancer activity against skin (B16F-10), brain (SF-268), colorectal (Caco-2 and HT-29) and ovarian (Sk-OV-3) cancer cells. 2-himachalen-7-ol (7-HC) was isolated using silica gel column chromatography, identified using GC-MS and confirmed with NMR studies. Cytotoxicity assays were performed using WST proliferation kit. Cell cycle analysis and cell apoptosis were evaluated using flow cytometry. The level of Akt, Erk, Bax and Bcl-2 proteins were determined via western blot analysis. Data revealed that 7-HC exhibits potent anti-proliferative activities against most treated cells, with B16F-10 being the most sensitive and Sk-OV-3 the least sensitive. Flow cytometry analysis demonstrated that the cytotoxicity of 7-HC is mediated via arresting the cell at Sub-G1 and inducing cell death via late apoptosis. Western blot analysis showed that treatment with 7-HC causes a downregulation of the level of anti-apoptotic proteins (Bcl-2) and an up-regulation of the level of pro-apoptotic proteins (Bax). A decline in the level of phosphorylated Erk and Akt was also noted. In conclusion, the current study revealed that 7-HC has a remarkable anticancer activity against a panel of cancer cell lines, an effect that may be partly attributed to the inhibition of the PI3K/Akt and MAPK/Erk pathways.